EXISTENCE OF REGIONAL LANGUAGES IN SUBMISSION OF ISLAMIC DAKWAH - Ahsan Aysar Amrul (Institut Agama Islam Negeri Palopo, 2019)
The role of language as a means to convey important Islamic dakwah. This paper reveals the existence of regional languages in it. Specific aspects of dakwah and additional personal aspects of mad'u are good formulas in achieving the goal of giving Islamic dakwah. The uniqueness of da'i by using regional languages will divide mad'u into certain choices. As for mad'u, a personal touch with the local language will generate interest and interest positively with the Islamic dakwah delivered